La circulation des ressources génétiques : évolutions juridiques et enjeux économiques - Sontot, Andrée; Mitteau, Martine; Lefort, Marianne (Cahiers Agricultures, 1999)
Plant genetic resources have been for several years subject to many international debates and concern. Public institutions, private firms and nongovernmental organisations are increasingly studying, consulting and taking position on the issues of genetic ressources conservation and sustainable utilisation. An increasing number of international fora also deal with such issues. Many legal frameworks have been elaborated to manage the exchange of genetic ressources: material transfer agreements, "triangular" coopération contracts, national legislation on access to genetic resources. This context explains how difficult it is for institutions and firms that maintain or use genetic reources to monitor, analyse and implement the evolution of the global international legal framework surrounding genetiv resources. In addition to this confusion, the situation created by the adoption of the Convention on Biological Diversity raises specific difficulties for the agricultural sector and for internation cooperation on food and agriculture. It is then of particular importance the national positions in the current negociations adopt a pragmatic, balanced approach reflecting these specificities.